Phenolic constituents with anti-inflammatory and cytotoxic activities from the rhizomes of Iris domestica. (November 2022) - Liu, Kai-Dong; Yang, Wan-Qi; Dai, Ming-Zhu; Xu, Yong; Qin, Yun-Peng; Dong, Ying-Ying; Fu, Jiang; Qu, Jing
Abstract: Four undescribed flavonoid glucosides (iridins B–C, tectoridin A and ampelopsinin A); one undescribed phenolic glucoside (diplostephioside B); one undescribed phenolic compound (phenanthrenetriol A); and seventeen known compounds were isolated from the rhizomes of Iris domestica. The chemical structures of the undescribed compounds were established by spectroscopic/spectrometric data interpretation using HRESIMS, NMR, and ECD. Tectoridin A, nigricin A and naringenin exhibited anti-inflammatory activities with inhibition rates of 53.71%, 57.68% and 88.71%, respectively, against the NF-κB signaling pathway at a concentration of 10 μM. 4′- O -methylnyasol (10 μM) exhibited 84.91% antiproliferative activity against the K562 human leukemia cell line with an IC50 value of 4.20 μM. Graphical abstract: Flavonoid glucosides and phenolic compounds from the rhizomes of Iris domestica, with potential anti-inflammatory activities. Image 1 HIGHLIGHTS: Six undescribed phenolic constituents were isolated from Iris domestica. Iridin B was rare xylopyranose substitution type in Iris domestica. The cytotoxic and NF-κB inhibitory activities for the isolated compounds were evaluated.